First-line nivolumab plus ipilimumab versus chemotherapy for the treatment of unresectable malignant pleural mesothelioma: patient-reported outcomes in CheckMate 743. (May 2022) - Scherpereel, Arnaud; Antonia, Scott; Bautista, Yolanda; Grossi, Francesco; Kowalski, Dariusz; Zalcman, Gérard; Nowak, Anna K.; Fujimoto, Nobukazu; Peters, Solange; Tsao, Anne S.; Mansfield, Aaron S.; Popat, Sanjay; et al.
Highlights: Patient-reported outcomes were assessed using EQ-5D and LCSS-Meso measures in CheckMate 743. Nivolumab + ipilimumab maintained overall health status in patients vs chemo. The risk of deterioration in symptoms was decreased with nivolumab + ipilimumab vs chemo. Nivolumab + ipilimumab delayed time to definitive deterioration in quality-of-life vs chemo. PRO data confirm clinical benefit of 1L nivolumab + ipilimumab vs chemo in unresectable MPM. Abstract: Objective: In CheckMate 743 (NCT02899299), nivolumab + ipilimumab significantly prolonged overall survival in patients with unresectable malignant pleural mesothelioma (MPM). We present patient-reported outcomes (PROs). Materials and Methods: Patients ( N = 605) were randomized to nivolumab + ipilimumab or chemotherapy. Changes in disease-related symptom burden and health-related quality of life (HRQoL) were evaluated descriptively using the Lung Cancer Symptom Scale (LCSS)-Mesothelioma (Meso) average symptom burden index (ASBI), LCSS-Meso 3-item global index (3-IGI), 3-level EuroQol 5-dimensional (EQ-5D-3L) visual analog score (VAS), and EQ-5D-3L utility index. PROs were assessed at baseline and every 2 (nivolumab + ipilimumab) or 3 weeks (chemotherapy) through 12 weeks, every 6 weeks through 12 months, every 12 weeks thereafter, and at specified follow-ups. Mixed-effect model repeated measures (MMRM) and time to deterioration analyses were conducted. Results: Completion rates were generally >80%. LCSS-Meso ASBI mean changes from baseline trended to improve over time with nivolumab + ipilimumab and deteriorate with chemotherapy, but did not meet clinically important difference thresholds [±10 score change]. EQ-5D-3L VAS mean scores improved over time with nivolumab + ipilimumab; by week 60, patients had scores consistent with United Kingdom normal population values. MMRM analyses favored nivolumab + ipilimumab for all individual symptoms except cough. Nivolumab + ipilimumab delayed time to definitive deterioration in HRQoL (hazard ratio 0.52 [95% confidence interval 0.36–0.74]) and showed a trend in symptom delay versus chemotherapy. Conclusions: Nivolumab + ipilimumab decreased the risk of deterioration in disease-related symptoms and HRQoL versus chemotherapy and maintained QoL in patients with unresectable MPM.